The 'language of the law' and the 'sentiment of the language'. A cultural challenge to enrich global English for comparative legal studies with national identities - Tieghi, Giovanna (Comparative Legilinguistics, 2025)
With the spread of the language and law theory in comparative constitutional law scholarship, the hegemony of the English language has often been overestimated, to the detriment of national cultural and linguistic identities. The worldwide ramifications of this reality, and in particular the related compelling role of the global dimension of the English language (Global English), have not entirely prevented the highly valuable process of adapting English to local needs. However, this aspect is still under-explored if we consider two related issues that are quite challenging: the perspective of Critical Discourse Analysis (CDA), which emphasizes the relationship between language and power, and the open-ended meanings of the languages spoken within national jurisdictions that encompass a variety of domains, with their multiple versions, idioms, or ‘Englishes’ of the Outer or Expanding Circle. Trying to respond to the transitional challenge of the role of English language in the field of comparative law studies, this paper elaborates some practical methodological suggestions. They are meant to promote a more pluralistic, legal-linguistic understanding of comparative constitutional law to attain an updated legal literacy in teaching (Content and Language Integrated Learning – CLIL) and research (Sentiment Legal Analysis – SLA) in the era of new technologies. Outlining the framework for the rigorous practice of interdiscursivity, it thus pursues the following normative arguments: (i) Achieving a balance between a common global register and nuances of meaning related to local areas requires a methodological design that considers context, legal discourse, and an interdisciplinary approach; (ii) Using the expanded field of SLA in constitutional law contributes to an updated investigation on English as a Court language; (iii) Taking judicial language as a case study of English-language court discourse in continental systems encourages research into the subjectivity of idiomatic and cultural expressions relating to the national identity of judicial attitudes.